Survival from XDR-TB is associated with modifiable clinical characteristics in rural South Africa. - Shenoi, Sheela V; Brooks, Ralph P; Barbour, Russell; Altice, Frederick L; Zelterman, Daniel; Moll, Anthony P; Master, Iqbal; van der Merwe, Theo L; Friedland, Gerald H (PloS one, 2012)
Drug-resistant tuberculosis (TB) is a major threat to global public health. Patients with extensively drug-resistant TB (XDR-TB), particularly those with HIV-coinfection, experience high and accelerated mortality with limited available interventions. To determine modifiable factors associated with survival, we evaluated XDR-TB patients from a community-based hospital in rural South Africa where a large number of XDR-TB cases were first detected.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Antitubercular Agents; Case-Control Studies; Coinfection; Extensively Drug-Resistant Tuberculosis; Female; HIV Infections; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Retrospective Studies; Risk Factors; South Africa